Assessment of nitrogen pollution reduction options in the river Nemunas (Lithuania) using FyrisNP model - Šileika, Antanas Sigitas; Wallin, Mats; Gaigalis, Kazimieras (Journal of Environmental Engineering and Landscape Management, 2013)
The paper quantifies and discusses diffuse and point sources total nitrogen (TN) inputs as well as retention and TN reduction options in the catchment of the main Lithuanian River Nemunas. Modelled average TN export between 2000–2006 from the River Nemunas catchment to the Baltic Sea was 37620 tonnes TN yr−1 according to the data oriented FyrisNP model. Loads of TN from diffuse and point sources as well as retention have been estimated for five subcatchments of the River Nemunas including the external load from Belarus. Agriculture contributes 74.6 to 89.5% of the TN load, increasing with the percentage of arable land and load from point sources. The main point source input is poorly treated wastewater at Kaunas city. The contribution from forest land to the TN load increases from 2.2% to 15.8% with an increase in forest land from 28.5 to 56.9% of the total subcatchments area. The highest retention of TN (30.7%) was observed in the Neris river subcatchment with the lowest hydraulic load (5.55 m yr−1). Scenario modelling suggests that the reduction target for Lithuania for nitrogen input to the Baltic Sea by 11700 tonnes can be achieved by installing biological treatment in sewage treatment plants in all district cities and by converting 20% of arable land to pastures or implementation of other equivalent measures in agriculture. Assessment of the FyrisNP model results shows that the model can be successfully applied for river basin management planning in catchments outside the area where the model originally has been developed. First published online: 11 Oct 2012